EFFECT OF PURPLE SWEET POTATO FIBER INTAKE ON BOWEL HABIT IMPROVEMENT IN PRESCHOOL CHILDREN - Siswi Wulandari; Bram Mustiko Utomo (Universitas STRADA Indonesia, 2026)
Functional constipation and irregular bowel habits in preschool children are often linked to low dietary fiber intake and are difficult to manage with practical, family-friendly strategies. This study evaluated a locally available, child-acceptable fiber source—purple sweet potato—as a feasible alternative to commercial fiber supplements. We used a quasi-experimental one-group pretest–posttest design over 14 days among 36 preschool children. Primary outcomes were bowel movement frequency, stool consistency, and constipation symptom score. Bowel movement frequency increased from 4.0±1.6 to 5.6±1.7 times/week (Δ=+1.6; p<0.001), stool consistency improved from 2.5±0.5 to 3.1±0.6 (Δ=+0.6; p<0.001), and constipation symptoms decreased from 3.2±1.1 to 1.9±1.2 (Δ=−1.3; p<0.001), with large effect sizes across outcomes. In conclusion, a two-week purple sweet potato–based fiber intervention was associated with meaningful improvements in bowel regularity, stool quality, and constipation-related symptoms. Daily monitoring supports its practical use in community and early childhood settings.